VEGETABLES GROUPPING BASED ON SUSTAINABLE AGRICULTURAL INDICATORS TO SUPPORT THE RURAL AGRO-INDUSTRIES IN PURBALINGGA REGENCY - Poppy Arsil dan Taufik Djatna (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTThe objectives of this research were to group vegetables cultivated in Karangreja district, Purbalingga, based on sustainable agriculture parameters and to evaluate each of cluster toward sustainable agriculture innitiatives. A simple random sampling technique was employed to select farmers as respondents in Serang and Kutabawa villages. Sustainable agricultural indicators and local government's indicators were used to group vegetables products. The indicators consisted of three aspects: environmental, economic, and socio-culture indicators. Cluster and scoring analysis were used to analyse data and related information. The result of this research produced four clusters of vegetables products. Based on the scoring analysis, tomato and beans were not towards sustainable agriculture, while big red chilly, potatoes and cabbages lead to support agriculture sustainable system.Keywords: agricultural sustainable system, cluster of horticultural products